The Role of Critical Reading Skill in Enhancing The Academic Competence of Law Students in The Context of International Law - Ruing, Fentry Hernaningsi; Jabu, Baso; Baa, Sultan; Sakkir, Geminastiti (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
Law students, especially those specializing in international law, encounter significant challenges regarding their critical reading abilities. Critical reading necessitates active engagement, compelling readers to think critically and employ various skills to identify key concepts, draw conclusions, make connections, anticipate purposes, analyze arguments, consider diverse perspectives, and evaluate ideas effectively. This research investigates the role of critical reading skills in enhancing the academic competence of law students within the context of international law. It employs a qualitative research design, utilizing case studies, interviews, and focus group discussions with fifth-semester students at the Faculty of Law, Muslim University of Indonesia. The findings reveal that critical reading skills significantly improve students' abilities to analyze complex legal texts, such as treaties and court decisions, by enabling them to identify key arguments, underlying biases, and contextual nuances. Structured frameworks, such as the SQ3R method and Legal Case-Based Reading (LCbR), are shown to foster deeper engagement with materials and facilitate the application of legal principles to real-world scenarios. Additionally, the study highlights the importance of exploring diverse perspectives, particularly those of marginalized groups, in enriching students' understanding of social and cultural implications. Ultimately, this research contributes to legal education reform by emphasizing the necessity of integrating critical reading skills into law curricula to better prepare students for the challenges of professional practice.